Direct oral anticoagulant approvals by four major regulatory agencies: a cross-sectional analysis of premarket and postmarket evidence - Joseph S Ross; Tianna Zhou; Maryam Mooghali (BMJ Open)
Objectives To compare the premarket and postmarket evidence of safety and efficacy of direct oral anticoagulants approved for stroke prevention in atrial fibrillation patients across four major regulatory agencies.Design Cross-sectional.Setting European Medicines Association (EMA), US Food and Drug Administration (FDA), Health Canada and Australian Therapeutic Goods Administration (TGA).Participants Apixaban, dabigatran, edoxaban and rivaroxaban marketing authorisations.Outcome measures Concordance among regulatory agencies with respect to (1) premarket evidence used to establish efficacy and safety and (2) postmarket safety boxed warnings and postmarketing study requirements.Results Apixaban, dabigatran and rivaroxaban were approved by each of the four regulatory agencies; edoxaban was only not approved by TGA. For premarket efficacy evidence, there was concordance across all agencies in terms of phase 3 trials for three (75%) drugs, sample size for three (75%) drugs, primary endpoints for four (100%) drugs, numerical results for three (75%) drugs, agency interpretation of results for four (100%) drugs and number of phase 2 trials for three (75%) drugs. For the premarket safety evidence, there was concordance across all agencies in terms of phase 3 trials for three (75%) drugs, sample size for two (50%) drugs, primary endpoints for four (100%) drugs, numerical results for three (75%) drugs, agency interpretation of results for three (75%) drugs and number of phase 2 trials for zero (0%) drugs. For postmarket safety information, FDA was the only agency that issued boxed warnings (for three (75%) drugs). Additionally, EMA and TGA required postmarketing studies (for four (100%) and two (50%) drugs, respectively), while FDA and Health Canada did not have any postmarketing requirements.Conclusions There was a high degree of concordance in the phase 3 trial premarket evidence used to establish efficacy and safety of direct oral anticoagulant approvals across four major regulatory agencies, but discordance in the phase 2 trial premarket evidence used, as well as in postmarket safety boxed warnings and postmarketing study requirements. These discrepancies highlight opportunities for further harmonisation in the evaluation and regulation of medical products globally.